2013
DOI: 10.1111/ejn.12169
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy failure in Alzheimer's disease and the role of defective lysosomal acidification

Abstract: Autophagy is a lysosomal degradative process to recycle cellular waste and eliminate potentially toxic damaged organelles and protein aggregates. The important cytoprotective functions of autophagy are evidenced by the diverse pathogenic consequences that may stem from autophagy dysregulation in a growing number of neurodegenerative disorders. In many of the diseases associated with autophagy anomalies, it is the final stage of autophagy-lysosomal degradation that is disrupted. In several disorders, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
255
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(270 citation statements)
references
References 75 publications
14
255
1
Order By: Relevance
“…In the current study, we found that V 0 ATPase is both oxidized and polyubiquitinated (DS vs. Ctr Y and Ctr O vs. Ctr Y), and we hypothesize that these modifications decrease the V 0 -ATPase proton pump activity consistent with autophagy dysfunction. Accordingly, the Nixon group has demonstrated reduced acidification of lysosomes in AD (73), and genetic mutation of lysosomal ATPase is among the risk factors recognized to contribute to autophagy-related neurodegenerative diseases (37,52). Furthermore, disturbance of autophagosome formation coupled with hyperactivation of the mTOR pathway is observed in DS brain, before and after development of AD pathology (59).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found that V 0 ATPase is both oxidized and polyubiquitinated (DS vs. Ctr Y and Ctr O vs. Ctr Y), and we hypothesize that these modifications decrease the V 0 -ATPase proton pump activity consistent with autophagy dysfunction. Accordingly, the Nixon group has demonstrated reduced acidification of lysosomes in AD (73), and genetic mutation of lysosomal ATPase is among the risk factors recognized to contribute to autophagy-related neurodegenerative diseases (37,52). Furthermore, disturbance of autophagosome formation coupled with hyperactivation of the mTOR pathway is observed in DS brain, before and after development of AD pathology (59).…”
Section: Discussionmentioning
confidence: 99%
“…Enlarged endosomes are the earliest neuronal pathology described in AD, and recent intriguing studies have implicated endocytic dysfunction, perturbations of vesicle trafficking, and lysosomal pH deficits in the mechanism of neurodegeneration (7,8). Several genes identified in genome-wide association studies of AD risk, including BIN1, PICALM, CD2AP, EPHA1, and SORL1, are known to be involved in endosomal mechanisms (9).…”
mentioning
confidence: 99%
“…Autophagy has been widely studied in relation to various diseases including AD. Failure in autophagy due to mutations in the PRESENILIN 1 gene has been implicated in AD [28]. To gain greater insight into autophagy, various animal models have been used to study the components of the autophagic pathway.…”
Section: Discussionmentioning
confidence: 99%